Intended Fallacies: Lowered Horizons, Ideological Inversions and Employed Intimacy. Translating Judita Vaičiūnaitė’s Early Poetry into Russian - Gintarė Bernotienė (Interlitteraria, 2016)
The case of the translations of Lithuanian poetess Judita Vaičiūnaitė (1937–2001) early poetry into Russian clearly illustrates the damages an original literary text (and the author’s institution) bore seeking to gain a statewide readership. In this article the Soviet translational practice of the 1960s is discussed as a phenomenon typical of Soviet literature when intentional rewriting, expurgation and ideological remakes of the authorial text were considered to be normal.